PERADABAN ISLAM DI NUSANTARA ERA WALISONGO DAN PERKEMBANGAN PENDIDIKAN - Ima Alfi Andini; M. Yulfan Setiawan; Anang Sholikhuddin (CV. BAROKAH PUBLISHER, 2026)
Character education is an effort to prevent the development of negative character traits In the younger generation, particularly through the introduction of local cultural values. The uniqueness of the Wali Songo can be said to resemble the Messengers of Allah SWT, Even though they did not receive Revelation and did not hold the title of prophet Or messenger of Allah SWT. The method used in this research is a descriptive qualitative Research method with a literature study approach that refers to several research data sources and Data collection techniques. This study focuses on the role of the Wali Songo in spreading Islam in Indonesia and their influence on the development of Islam within society